How Hope and Doubt Affect Climate Change Mobilization - Marlon, Jennifer R.; Bloodhart, Brittany; Ballew, Matthew T.; Rolfe-Redding, Justin; Roser-Renouf, Connie; Leiserowitz, Anthony; Maibach, Edward (Frontiers in Communication, 2019)
The severe threats posed by anthropogenic climate change make hope and a sense of efficacy key ingredients in effective climate communication. Yet little is known about what makes individuals hopeful – or in contrast, doubtful – that humanity can reduce the problem, or how hope relates to activism. This study uses mixed-methods with two national surveys to 1) identify what makes people hopeful or doubtful that humanity will address the problem (Study 1, N = 674), and 2) whether hopeful and doubtful appraisals are related to activism or policy support (Study 2, N = 1,310). In Study 1, responses to open-ended questions reveal a lack of hope among the public. For those with hope, the most common reason relates to social phenomena – seeing others act or believing that collective awareness is rising (“constructive hope”). Hope for some, however, stems from the belief that God or nature will solve the problem without the need for human intervention (which we call “false hope”). The most prevalent doubts are low prioritization, greed, and intergroup conflict (i.e., the need for cooperation at various scales to successfully address the issue). We identified both “constructive” and “fatalistic” doubts. Constructive doubts are concerns that humanity won’t address the problem effectively, while fatalistic doubts are beliefs that we can’t address the problem even if we wanted to because it is in the hands of God or Mother Nature. Study 2, we used these emergent hope and doubt appraisals to develop survey measures. Regression analyses suggest that constructive hope and doubt predict increased policy support and political engagement, whereas false hope and fatalistic doubt predict the opposite. An interaction exists between constructive hope and doubt in predicting political behavioral intentions, which suggests that having hope that humans will reduce climate change, along with recognition that humans are not doing enough may also be constructive and motivate political action. Climate change communicators might consider focusing on constructive hope (e.g., human progress, the rise of clean energy), coupled with elements of constructive doubt (e.g., the reality of the threat, the need for more action), to mobilize action on climate change.